Novel Bismuth-Oxyhalide-Based Materials and their Applications - Gondal, Mohammed A.; Xiaofeng, Chang; Dastageer, Mohamed A. (Advanced Structured Materials, 2017)
This book provides a comprehensive overview of a series of bismuth oxyhalide compounds of BiOX (X=F, Cl, Br, I), in terms of their microstructure, electronic/band structure, preparation techniques, optical properties and their applications. The book brings together, for the first time, a compilation of advances in this area, including results achieved at the authors' lab (such as ultra-microscopy characterization by means of aberration-corrected STEM), offering a valuable guide for researchers and students alike.